2022
DOI: 10.1186/s12871-022-01703-8
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of intravenous and inhalation anesthesia after pancreatic cancer resection: a retrospective study

Abstract: Background Different types of anesthesia may affect cancer patient’s outcomes, we compared the overall survival (OS) and disease-free survival (DFS) of patients with pancreatic cancer under total intravenous and inhalation anesthesia. Methods The authors collected the electronic medical records of patients who had accepted at a pancreatectomy from January 1, 2010 to December 31, 2016. Patients respectively received total intravenous anesthesia (TIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Forty-two retrospective cohort studies and two RCTs with a total of 686,923 patients were included in this study [ [19] , [20] , [21] , [22] , [23] , [24] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] ]. Thirty-five trials were single-center studies [ 19 , [21] , [22] , [23] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [50] , [51] , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty-two retrospective cohort studies and two RCTs with a total of 686,923 patients were included in this study [ [19] , [20] , [21] , [22] , [23] , [24] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] ]. Thirty-five trials were single-center studies [ 19 , [21] , [22] , [23] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [50] , [51] , …”
Section: Resultsmentioning
confidence: 99%
“…Types of cancer surgery and inhalation anesthetics varied between studies. In total, two studies enrolled participants undergoing surgery for glioblastoma [ 47 , 56 ], one study for oral cancer [ 63 ], nine studies for breast cancer [ 34 , 37 , 42 , 45 , 49 , 53 , 59 , 61 , 71 ], five studies for non-small cell lung cancer [ 38 , 55 , 60 , 65 , 69 ], two studies for esophageal cancer [ 36 , 68 ], four studies for gastric cancer [ 40 , 44 , 50 , 57 ], five studies for colorectal cancer [ 34 , 39 , 48 , 54 , 62 ], four studies for hepatobiliary cancer [ 19 , 41 , 43 , 51 ], two studies for pancreatic cancer [ 52 , 64 ], two studies for gynecological cancer [ 21 , 22 ], two studies for urological cancer [ 23 , 58 ], one study for osteosarcoma [ 66 ], and six studies for various cancers [ 20 , 24 , 35 , 46 , 68 , 70 ]. For inhalation anesthetics, seventeen studies used sevoflurane to maintain anesthesia [ 19 , 21 , 34 , 38 , 40 , [47] , [48] , [49] , 53 , 59 , [62] , [63] , [64] , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a national Danish registry study showed that propofol-based TIVA is associated with better survival outcomes after colorectal cancer surgery [28]. However, other previous studies reported no association between propofol-based TIVA and mortality after gastric and pancreatic cancer surgery [29,30]. Further This article is protected by copyright of Korean Journal of Anesthesiology.…”
Section: Discussionmentioning
confidence: 99%
“…Whether different anesthetics can affect the prognosis of tumor patients is still controversial. In a retrospective study of the overall survival of pancreatic cancer patients with different anesthesia methods showed TIVA and IHNA for improved OS in pancreatic patients or DFS was not significant [ 11 ]. Another study showed that TIVA was not significantly associated with a reduction in overall 1-year mortality or cancer-related mortality after gastric cancer surgery compared to IHNA [ 12 ].…”
Section: Discussionmentioning
confidence: 99%